Importance of Biochemical Analysis of Postmortem Intraocular Fluid Regarding to Time and Cause of Death - Teyin, Muharrem; Balcı, Yasemin; Uslu, Sema; Karbeyaz, Kenan; Özdamar, Kazım (The Bulletin of Legal Medicine, 2015)
Aim: The time of the death has been one of the questions frequently inquired by courts to the forensic medicine experts. In this study, it is aimed to investigate the relationship between cause of death and postmortem interval with can easily be detected in postmortem intraocular fluid samples and routine biochemical tests. Materials and Methods: A total of 100 cases autopsied at the Eskisehir Osmangazi University whose exact times of the death were known has been included in the study. Cases were divided into 3 groups as 10 hour and below postmortem interval, 10-20 hours and upon 20 hours. The cause of death was divided into two groups as traumatic and non-traumatic. Results: In this study the significant relationship was determined between potassium and uric acid levels and postmortem interval. It is determined that the mean level of Sodium and Chlorine sow difference in patients died because of traumatic and non-traumatic reasons. Key words: Postmortem biochemistry, Vitreous humor, Time since death, Cause of death.